PRAKTIK TRILOGI PENDIDIKAN KI HAJAR DEWANTARA DALAM PEMBENTUKAN KARAKTER MANDIRI DI SMAN 1 KRIAN SIDOARJO - Iskandari, Helen Octania; Jatiningsih, Oksiana (Universitas Negeri Surabaya (Unesa), 2024)
Character education through the Pancasila Student Profile is highly emphasized in the Independent Curriculum, one of which is independent character. However, there are still students whose learning independence is still relatively lacking, such as students who do not have the initiative to learn independently, who still have the habit of copying their friends' work, complaining when given assignments, and so on. Teachers can teach and educate students' character through the Among Method. The Among Method by Ki Hajar Dewantara emphasized that teachers should be able to use this method in the learning process through the motto which became known as the Educational Trilogy